Method of constructing a secure and trustable industrial control system in smart power plant - Wang Xiang; Shen Zhiwei; Zhu Xiaoman; Guo Shuo; Li Ling (Dianzi Jishu Yingyong)
With the rapid advancement of informatization construction of power plants, industrial control systems will achieve a high degree of digitization and intelligence, which puts forward higher requirement for the calculation, storage and safety protection capabilities of traditional control system. Based on the PK system of China Electronics Corporation(CEC), this paper proposes a secure and trustable industrial control system in smart power plant. The cloud edge collaboration can effectively improve the capability of edge computing and the level of intelligence based on automatic prediction and independent decision-making mechanism. Besides, based on the network security protection regulations, a cloud-network-end integrated active defense system is proposed.